Thus says the Lord : essays on the Former and Latter Prophets in honor of Robert R. Wilson - Wilson, Robert R., 1942-; Ahn, John J.; Cook, Stephen L., 1962- (Library of Hebrew Bible/Old Testament studies, 2009)
This work assembles contributions from North America''s leading Hebrew Bible/Old Testament scholars in honor of a highly respected biblical scholar, whose work on biblical prophets has been especially influential. Within the list are former teachers, current colleagues, and former students who are now colleagues in their own right, representing a wide range of denominational traditions represented-Roman Catholics, Lutheran, Episcopal, Presbyterian, etc. The book is divided into major two sections with a brief introduction by the editors, John Ahn and the Stephen Cook. Here, a brief biograph.